SISTEM INFORMASI PELACAKAN KERUSAKAN LAPTOP DENGAN DUKUNGAN MODUL SISTEM PAKAR - Satya Wibawa Putra, Made Ngurah; Care Khrisne, Duman; Wijaya, I Ketut (Jurnal SPEKTRUM, 2021)
Thexhighxusexofxlaptops today by individuals will affect the condition of laptop and causing various damage to the laptop itself. The limited knowledge by user solving the problems on a laptop make user have to consult an expert technician to obtain a solution for existing damage. On the other hand, many and varied defects of laptops, as well as the hectic tasks that must be performed by technicians, causing problems on the side of technicians.xUtilizationxofxinformation technologyxcanxbexaxsolutionxtoxovercomexproblems between users and technicians. By building a web-based expert system to get the result of damage diagnosis and repair solutions, hopefully it can help users find out what problems on their laptop and make it easier for technician to deal with damage. This research using webbased forward chaining as system method. This system can display the results of a laptop damage diagnosis that it come from symptoms asked by system and repair solution from damage diagnosis. Basedxonxthextestxresultsxusingxblack boxxmethod,xthexsystems has function that according with system design, can run according to orders, and havexbeenxdeclaredxsuccessful.xBasedxonxthexresultxofxthexSystemxUsability Scalex(SUS)xtest, this system obtainxscorex82.5, which means that the whole system can be accepted as functioning well on the web.